Mutagenesis of avian carcinoma virus MH2: only one of two potential transforming genes (delta gag-myc) transforms fibroblasts. - Zhou, R P (1985)
Avian carcinoma virus MH2 contains two potential transforming genes, delta gag-mht and delta gag-myc. Thus, MH2 may be a model for two-gene carcinogenesis in which transformation depends on two synergistic genes. Most other directly oncogenic viruses contain single, autonomous transforming (onc) genes and are models for single-gene carcinogenesis. To determine which role each potential onc gene of MH2 plays in oncogenesis, we have prepared deletion and frameshift mutants of each of the two MH2 genes by in vitro mutagenesis of cloned proviral DNA and have tested transforming function and virus production in cultured primary quail cells. We have found that mht deletion mutants and wild-type virus transform primary cells and that myc deletion and frameshift mutants do not. The morphologies of cells transformed by the mht deletion mutants and by wild-type MH2 are similar yet vary considerably. Nevertheless, typical mutant transformed cells can often be distinguished from cells transformed by wild-type MH2. We conclude that the delta gag-myc gene transforms primary cells by itself, without the second potential onc gene. This myc-related gene is the smallest that has direct transforming function. delta gag-mht is without detectable transforming function but may affect transformation by delta gag-myc. Thus, MH2 behaves like a virus with a single onc gene, although it expresses two potential onc genes, and it appears not to be a model for two-gene carcinogenesis. Further work is necessary to determine whether the delta gag-mht gene possibly enhances oncogenic function of delta gag-myc or has independent oncogenic function in animals.